Surface‐Engineered Ti3C2Tx with Tunable Work Functions for Highly Efficient Polymer Solar Cells. Issue 21 (21st April 2022) - Hou, Chunli; Huang, Chengwen; Yu, Huangzhong; Shi, Shengwei
Abstract: Ti3 C2 T x, as a newly investigated 2D material, has gained great attention owing to its metallic conductivity, tunable work function ( W F ), and unique electrical property. However, its W F can be further adjusted to meet the needs of optoelectronic devices. Here, surface‐engineered Ti3 C2 T x is fabricated with tunable W F by treating with ethanolamine and rhodium chloride (RhCl3 ). Ethanolamine treated Ti3 C2 T x can induce the chemical adsorption of NH2 on Ti3 C2 T x with hydrogen‐bonding, which causes the decreased W F, while chemical doping with RhCl3 leads to the improvement of W F, which is achieved by the downshift of Femi level of Ti3 C2 T x . Moreover, the ethanolamine and RhCl3 can effectively passivate the vacancies of Ti. As such, the surface‐engineered Ti3 C2 T x is more suitable as buffer layer for polymer solar cells (PSCs) by enhancing the interfacing characteristics of the Ti3 C2 T x /active layer. The PSCs with engineered Ti3 C2 T x for electron or hole transport layers can exhibit a power conversion efficiency of 15.88% or 15.54%. These efficiencies can be compared with those of devices with a conventional transport layer. This work provides a facile strategy to realize the work function tunability of Ti3 C2 T x, and also shows that the tuned Ti3 C2 T x has a certain application prospect in photovoltaic devices. Abstract : Here, methods to tune the work function of Ti3 C2 T x are presented and the Ti vacancies in Ti3 C2 T x are passivated by treatment with ethanolamine and metal chloride RhCl3 . The polymer solar cells with engineered Ti3 C2 T x for electron or hole transport layers exhibit a power conversion efficiency of 15.88% or 15.54%. The modified Ti3 C2 T x has a certain application prospect in photovoltaic devices.